Networked Libraries Promoting Lifelong Learning - Myroni, Victoria; Pombortsis, Andreas (Proceedings of the International Conference on Networked Learning, 2008)
Lifelong Learning may be provided by schools, institutions, professional bodies, private learning companies, community projects or training departments within businesses. Not only will learners be able to match the availability of courses with their requirements, but record their achievements, perhaps building an online portfolio of their experience. To achieve this, many different organisations with varying methods of storing learner details will have to interact with one another. After a period of time, intelligent services may seek out the most appropriate courses based on the learner’s profile, requirements and information available from the multitude of learning providers and brokers. Our research uses the description of the content using metadata and presents a framework supporting the delivery of learning content to distribute and categorize academic content and to provide content catalogues and specific educational content to the target groups. Library services to support adult and lifelong learning have developed in response to changes in the higher education system (distance learning, part-time study, franchising of courses), with developments in adult and further education and open learning, and in response to demands from independent learners. The basic operation of an e-educational organization is to provide e-lectures, e-labs, supporting contents and e–libraries (acquisition, cataloguing, circulation and serials control). In the case of e-libraries the vast information sources, are not only the items held by or owned by the library, but also include remote information sources. Providing access to remote sources is a challenge for modern educational systems. The suggested environment helps the learners to focus on the knowledge and skills necessary for the fulfillment of work-based objectives and involves a more in-depth assessment of particular areas of professional knowledge. The environment under discussion can be used for library automation activities, thus libraries can increase buying power and access to sources, through qualitative resource sharing. Some institutions have developed sophisticated levels of services facilitated by the development of new technologies, including electronic information networks. The new role of Libraries is how to provide not only information but also real knowledge. It is interesting to see how Libraries and Open Academic Institutions can be real e-educators by making alterations to their structure, service systems and functions. Libraries need extra support to respond to the challenges that are broadly associated with information technology, which affects the nature of information resources. Cooperation among libraries is essential. New alliances also have to be forged with other kinds of cultural institutions and repositories. Interdependency of academic libraries cannot mean self-reliance. Modern demands formulate the sharing of not only resources but also the functions and roles inside a well-organized framework, respecting the particularities of each. National Libraries will have to change their roles from ´gatekeepers´ to ´gateways´ of knowledge and in this way they should perform such tasks as information mapping, information audits, training in information literacy, and information of best practices and help their users to navigate the world of information more meaningfully. As a result, statistics can be gathered and attention should be given to the following parameters: (1) Understanding Customer’s Needs, (2) .Community Profiling and as a consequence designing should be geared to (1) Market Segmentation (2) Marketing Plan (3) Marketing Audit and (4) Objectives. A number of programmes such as PROLIX, CAEL, CLEO have been developed which have allowed universities to link education to the workplace, and thus give students the chance to acquire skills which could be useful in their working lives. The paper suggests the concept of learning through networks as a challenging concept for addressing user-driven technologies that support creative learning processes. Adult and lifelong learning represent an increasingly essential part of the portfolio of traditional educational institutions.